URGENSI REDENOMINASI NILAI RUPIAH DALAM PEREKONOMIAN INDONESIA - NILASARI, ERISSA (Islamic Economics and Business Faculty of UIN Antasari, 2014)
In order to overcome inflation, many countries are employing currency redenomination policy. This is a public policy measure that simplifies the use and managing of the national currency of a country, through its expression in a new and smaller equivalent scale. The goal of rupiah redenomination is to simplify the currency scale in accounting record systems and monetary statements, to strengthten rupiah value, and also to promote the equal growth of social and economical development of the country. Beforehand, low average inflation and economy stability as the demanded factors for currency redenomination policy should be performed by the respected countries. Indonesia is already in this state of ideal economy condition for the policy. In spite of that; due to inadquate preparations, insufficient expense planning, and lack of citizen promptitude; therefore, rupiah redenomination policy is not immediately employed.